Screening Prospective Investors - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance to governments on how to screen and select prospective investment projects to ensure they maximize the social, economic, and environmental benefits while minimizing the risks. It provides investors information on what can be expected in cases of good screening practice. The acceptance of investors that later fail financially or have poor social and environmental outcomes has had damaging impacts on many countries as well as communities. Screening investors is a critical component of a country’s policy framework to mitigate those risks and to improve the likelihood that investments will have a positive effect on sustainable development priorities. This note summarizes available resources on how to screen agricultural investments and calls on donors, international organizations, and civil society to develop more. It is complemented by note 7: tools for screening investors, which provides a detailed toolkit that can be adapted to host countries’ individual circumstances.